A method for preparing a fuel cell graphite composite plate and a graphite composite plate made therefrom
By using phenolic resin and modified carbon fiber, combined with raw material granulation and hot pressing treatment, the problem of resin flow aggregation during the hot pressing process of graphite composite plate is solved, and the uniformity and high performance of graphite composite plate are achieved, reducing the adverse impact on fuel cell performance.
Patent Information
- Application Number
- CN202411782856.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
During the hot pressing process of existing graphite composite bipolar plates, the thermosetting resin is prone to flow and gather on both sides of the mold, resulting in an increase in contact resistance between the composite plate and the membrane electrode, affecting the performance of the fuel cell.
Phenolic resin is used as the thermosetting resin, and the graphite composite powder is granulated, dried, cooled and crushed, so that it can be transformed from wet to dry state, reducing the possibility of resin flow. Then evenly lay the material in the mold and hot pressing treatment is performed to ensure that the resin is further cross-linked and cured at high temperature to form a uniform graphite composite plate.
Through this method, the contact resistance between the graphite composite plate and the membrane electrode is reduced, the performance of the fuel cell is improved, and the production efficiency and the storage convenience of the material are improved.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of fuel cells, and more specifically, to a method for preparing a fuel cell graphite composite plate and the graphite composite plate prepared therefrom. Background Art
[0002] Based on the matrix material, bipolar plates can be mainly divided into three categories: metal bipolar plates, graphite bipolar plates and graphite composite bipolar plates. Graphite composite bipolar plates are made of organic polymer resin and carbon-based conductive fillers as the main raw materials. Among them, the resin matrix enhances the mechanical properties and bonds the conductive fillers. The conductive fillers represented by graphite form a conductive network in the composite material to realize the electrical and thermal conductivity of the composite graphite bipolar plate.
[0003] At present, graphite composite bipolar plates are mainly produced by mixing graphite powder and resin evenly and then molding them. In terms of resin selection, if thermoplastic resin is used, there will be problems such as low strength, complex mixing process, low conductivity, long mold cooling time and low efficiency. Therefore, thermosetting resin is usually used.
[0004] However, since thermosetting resins are generally oligomer solutions or liquid monomers, the resulting graphite composite powder is in a wet state. During the hot pressing process, the resin flows and gathers on both sides of the mold, which can easily increase the contact resistance between the composite plate and the membrane electrode, thereby adversely affecting the performance of the fuel cell. Summary of the invention
[0005] In order to reduce the adverse effect of the contact resistance between the composite plate and the membrane electrode on the performance of the fuel cell, the present application provides a method for preparing a fuel cell graphite composite plate and the graphite composite plate prepared therefrom.
[0006] In the first aspect, the present application provides a method for preparing a fuel cell graphite composite plate, which adopts the following technical solution:
[0007] A method for preparing a fuel cell graphite composite plate comprises the following steps:
[0008] S1, raw material granulation: weigh 201±10 parts of graphite composite powder and spread it evenly on a flat plate, dry it at 90-150°C for 10-30min, and crush it after cooling to obtain composite powder particles with a particle size of 200±100 mesh, wherein the graphite composite powder includes a first graphite composite powder, which is prepared by mixing 160-180 parts of 200±100 mesh graphite powder, 20-40 parts of phenolic resin and 0.5-1.5 parts of filler, wherein the filler includes carbon fiber;
[0009] S2. Evenly spread the prepared composite powder particles into a mold, heat and hot-press after the mold is closed to obtain a fuel cell composite graphite plate.
[0010] By adopting the above technical solution, a thermosetting resin, namely a phenolic resin, is used to reduce the possibility that the resin is sensitive to the mold opening temperature, thereby increasing production efficiency. The first graphite composite powder is obtained by mixing graphite powder, phenolic resin and carbon fiber, and the first graphite composite powder is secondarily powdered by mixing, drying, cooling and crushing the obtained first graphite composite powder. At this time, the phenolic resin is initially cross-linked and solidified and evenly coated on the outside of the graphite powder, so that the first graphite composite powder is converted from a wet state to a dry state, which is convenient for storage, and the obtained first graphite composite powder particles are uniform, which is convenient for distributing the first graphite composite powder, thereby reducing the possibility of uneven density in various parts of the obtained graphite composite plate, and at the same time, reducing the possibility that the phenolic resin flows and gathers on both sides close to the mold during the hot pressing and mixing of the first graphite composite powder, thereby increasing the contact resistance between the obtained graphite composite plate and the membrane electrode, thereby reducing the adverse effects on the performance of the obtained fuel cell.
[0011] Preferably, in the step S2, heating and hot pressing comprises the following steps:
[0012] After the mold is closed, the mold containing the graphite composite powder particles is placed at a temperature of 150-180° C. for hot pressing for 30-60 minutes, and the hot pressing pressure is 20-40 MPa.
[0013] By adopting the above technical scheme, the mixed and secondary granulated graphite composite powder particles are filled in a mold, and the mixed graphite composite powder is hot pressed within the above temperature, time and pressure range. At this time, the phenolic resin in the graphite composite powder particles is further cross-linked, cured and polymerized at high temperature to form a graphite composite plate. At this time, since the phenolic resin is evenly coated on the outside of the graphite powder, the possibility of the phenolic resin accumulating near the two sides of the mold under the drive of pressure is reduced, thereby reducing the adverse effect on the contact resistance between the obtained graphite composite plate and the membrane electrode; when the temperature and pressure are less than the above range, it is difficult for the resin to fully cross-link and cure completely, which may easily cause the obtained graphite composite plate to have insufficient strength and reduce the service life; when the temperature and time exceed the above range, it is easy to cause the possibility of decomposition of the phenolic resin, and when the pressure exceeds the above range, it is easy to cause the possibility of damage to the mold, thereby causing an adverse effect on production efficiency.
[0014] Preferably, the graphite composite powder also includes a second graphite composite powder, the weight ratio of the first graphite composite powder to the second graphite composite powder is 1: (1±0.1), and the second graphite composite powder is prepared by mixing 180-200 parts of 200±100 mesh graphite powder, 5-15 parts of phenolic resin and 0.5-1.5 parts of filler, and the filler includes carbon fiber.
[0015] By adopting the above technical scheme, the first graphite composite powder and the second graphite composite powder are compounded in the above ratio to obtain the graphite composite powder, so that the phenolic resin content of the prepared graphite composite plate close to the flow field side is reduced, further reducing the possibility of the phenolic resin gathering on both sides close to the mold under pressure, and reducing the adverse effect on the contact resistance between the prepared graphite composite plate and the membrane electrode.
[0016] Preferably, the method for preparing a fuel cell graphite composite plate comprises the following steps:
[0017] S1, raw material granulation: weigh the first graphite composite powder according to the proportion and evenly spread it on a flat plate, dry it at 90-150°C for 10-30min, and crush it after cooling to obtain the first composite powder particles with a particle size of 200±100 mesh; weigh the second graphite composite powder according to the proportion and evenly spread it on a flat plate, dry it at 90-150°C for 10-30min, and crush it after cooling to obtain the second composite powder particles with a particle size of 200±100 mesh;
[0018] S2. Evenly spread the prepared first composite powder particles into a mold, place the mold containing the first graphite composite powder particles at a temperature of 30-50° C. for pre-pressing for 5-10 min, and the pre-pressing pressure is 2-5 MPa. After the pressure is released, evenly distribute the second graphite composite powder particles on the flow field side of the pressed first graphite composite powder, and after closing the mold, place it again at a temperature of 150-180° C. for hot pressing for 30-60 min, and the hot pressing pressure is 20-40 MPa to obtain a graphite composite plate.
[0019] By adopting the above technical scheme, the first graphite composite powder is spread on the mold, and the first graphite composite powder is initially formed into a plate shape by low temperature and low pressure pre-pressing, thereby reducing the possibility of the second graphite composite powder and the first graphite composite powder being mixed when the second graphite composite powder is laid, and at the same time reducing the possibility of the phenolic resin in the first graphite composite powder melting and accumulating on both sides close to the mold. At this time, the second graphite composite powder particles are laid on the flow field side of the graphite composite plate, and the first graphite composite powder and the second graphite composite powder are formed into a graphite composite plate by hot pressing, thereby realizing the gradient distribution of the phenolic resin in the graphite composite plate, improving the contact impedance, and reducing the adverse effect of the contact resistance between the graphite composite plate and the membrane electrode on the performance of the fuel cell.
[0020] Preferably, the carbon fiber is a modified carbon fiber, and the modified carbon fiber is prepared by grafting carboxymethyl cellulose onto carbon fiber via 3-aminopropyltriethoxysilane.
[0021] Preferably, the weight ratio of the carboxymethyl cellulose, 3-aminopropyltriethoxysilane and carbon fiber is 1:(92-100):(2-4).
[0022] By adopting the above technical scheme, carboxymethyl cellulose is grafted onto carbon fiber through 3-aminopropyltriethoxysilane, thereby modifying the carbon fiber so that the carboxymethyl cellulose chains grafted on the carbon fiber can overlap with the phenolic resin and form a mutually bonded network structure in the prepared graphite composite plate, thereby enhancing the interfacial bonding strength between the carbon fiber and the resin matrix and improving the mechanical properties of the graphite composite plate.
[0023] Preferably, the modified carbon fiber is prepared by the following steps:
[0024] A1. Surface oxidation: The carbon fiber is placed in a concentrated nitric acid solution, treated at room temperature for 30-150 minutes, washed to a pH of 7±1, and then dried to obtain a surface-treated carbon fiber;
[0025] A2. Silanization: Dissolve 3-aminopropyltriethoxysilane in a methanol solution with a mass fraction of 90±1% according to a certain proportion and mix well. Add the obtained surface-treated carbon fiber into the solution and mix for 2±1h, then filter out the fiber and dry it for 24±1h to obtain silanized carbon fiber.
[0026] A3. Graft modification: Carboxymethyl cellulose is added to deionized water in proportion and mixed evenly, silanized carbon fiber is added to the mixture, and mixed at a temperature of 60-80° C. for 2-3 hours, filtered and dried to obtain modified carbon fiber.
[0027] By adopting the above technical scheme, the surface of the carbon fiber is oxidized, so that the surface of the carbon fiber is oxidized to form carboxyl groups, hydroxyl groups and acidic groups, 3-aminopropyltriethoxysilane is grafted with the carbon fiber after surface oxidation to form silanized carbon fiber, and the silanized carbon fiber is added to the carboxymethyl cellulose aqueous solution and mixed at the above temperature and time. At this time, the carboxymethyl cellulose is grafted on the silanized carbon fiber, thereby modifying the carbon fiber, increasing the bonding force between the carbon fiber and other raw materials, and forming a tree-like structure of the modified carbon fiber, which is convenient for the grafted carboxymethyl cellulose to overlap with the phenolic resin, thereby enhancing the interfacial bonding strength between the carbon fiber and the resin matrix, and improving the mechanical properties of the graphite composite plate.
[0028] In the second aspect, the present application provides a fuel cell graphite composite plate, which adopts the following technical solution:
[0029] A fuel cell graphite composite plate is prepared by the above-mentioned fuel cell graphite composite plate preparation method.
[0030] By adopting the above-mentioned technical scheme, the fuel cell graphite composite plate prepared by the preparation method of the present application can meet the use requirements of the fuel cell graphite composite plate. While facilitating the distribution of materials and improving production efficiency, the prepared graphite composite plate has a uniform texture, and the phenolic resin is distributed in the graphite composite plate in a ladder-like manner, which reduces the contact resistance between the prepared graphite composite plate and the membrane electrode, thereby reducing the adverse effects on the performance of the fuel cell.
[0031] In summary, this application has the following beneficial effects:
[0032] 1. A thermosetting resin, i.e., phenolic resin, is used to mix graphite powder, phenolic resin and carbon fiber to obtain a first graphite composite powder, and the first graphite composite powder is mixed, dried, cooled and crushed to make a second powder of the first graphite composite powder, so that the first graphite composite powder is converted from a wet state to a dry state for easy storage, and the particles of the first graphite composite powder are uniform, which is convenient for distributing the first graphite composite powder, reducing the possibility of uneven density of the obtained graphite composite plate, and reducing the possibility of phenolic resin flowing and gathering on both sides close to the mold during the hot pressing and mixing of the first graphite composite powder, thereby increasing the contact resistance between the obtained graphite composite plate and the membrane electrode, thereby reducing the adverse effect on the performance of the obtained fuel cell.
[0033] 2. The first graphite composite powder and the second graphite composite powder are subjected to secondary granulation respectively, so that the first graphite composite powder and the second graphite composite powder are formed into particles with phenolic resin wrapped around the outside of the graphite powder, the prepared first graphite composite powder particles are spread in a mold and hot pressed, and after the hot pressing is completed, the prepared second graphite composite powder is spread on the flow field side of the graphite composite plate and hot pressed, so that the first graphite composite powder and the second graphite composite powder form a dense graphite composite plate, at this time, the resin content on the flow field side of the prepared graphite composite plate is reduced, and a gradient distribution of the resin content in the prepared graphite composite plate is achieved, the contact impedance is improved, and the adverse effect of the contact resistance between the graphite composite plate and the membrane electrode on the performance of the fuel cell is reduced.
[0034] 3. Spread the first graphite composite powder flat on the mold, and use low temperature and low pressure pre-pressing to make the first graphite composite powder initially form a plate shape, reduce the possibility of the second graphite composite powder and the first graphite composite powder mixing when the second graphite composite powder is laid, and reduce the possibility of the phenolic resin in the first graphite composite powder melting and accumulating on both sides close to the mold. At this time, spread the second graphite composite powder particles on the flow field side of the graphite composite plate, and use hot pressing to form the first graphite composite powder and the second graphite composite powder into a graphite composite plate, so as to achieve a gradient distribution of the phenolic resin in the graphite composite plate, improve the contact impedance, and reduce the adverse effects of the contact resistance between the graphite composite plate and the membrane electrode on the performance of the fuel cell. DETAILED DESCRIPTION
[0035] The present application is further described in detail below with reference to the embodiments.
[0036] The thickness uniformity detection method, surface resistivity detection method and contact resistance detection method of the graphite composite plates prepared in all embodiments and comparative examples are as follows:
[0037] 1. Thickness uniformity
[0038] The thickness uniformity of the graphite composite plate is tested according to the test method of the national standard GB / T 20042.6-2024 "Proton Exchange Membrane Fuel Cell Part 6: Bipolar Plate Characteristics Test Method".
[0039] 2. Surface resistivity
[0040] The surface resistivity of the graphite composite plate is tested according to the detection method of the national standard GB / T 20042.6-2024 "Proton Exchange Membrane Fuel Cell Part 6: Bipolar Plate Characteristics Test Method".
[0041] 3. Contact resistance
[0042] The contact resistance of the graphite composite plate is tested according to the test method of the national standard GB / T 20042.6-2024 "Proton Exchange Membrane Fuel Cell Part 6: Bipolar Plate Characteristics Test Method".
[0043] 4. Bending strength
[0044] The bending strength of the graphite composite plate is tested according to the test method of the national standard GB / T 20042.6-2024 "Proton Exchange Membrane Fuel Cell Part 6: Bipolar Plate Characteristics Test Method".
[0045] raw material
[0046] The raw materials in the examples and comparative examples of the present application can be obtained from commercial sources, wherein the concentration of the concentrated nitric acid solution is 68%.
[0047] Preparation Example
[0048] Preparation Example 1 Modified Carbon Fiber
[0049] Preparation Example 1.1
[0050] A modified carbon fiber is prepared by the following steps:
[0051] A1. Surface oxidation: 164.95 g of carbon fiber was placed in a concentrated nitric acid solution, treated at room temperature for 30 min, washed to a pH of 7, and then dried to obtain a surface-treated carbon fiber;
[0052] A2. Silanization: Dissolve 3793.81 g of 3-aminopropyltriethoxysilane in a 90% by mass methanol solution according to the proportion and mix well. Add the obtained surface-treated carbon fiber into the solution and mix for 2 hours. Then filter out the fiber and dry it for 24 hours to obtain silanized carbon fiber.
[0053] A3. Graft modification: 41.24 g of carboxymethyl cellulose was added to deionized water in proportion and mixed evenly. The silanized carbon fiber was added to the mixture and mixed at 60° C. for 2 h. The modified carbon fiber was obtained after filtering and drying.
[0054] Preparation Example 1.2-1.5
[0055] Different from Preparation Example 1.1, the raw material ratios and process parameters of the modified carbon fibers in Preparation Examples 1.2-1.5 are different, see Table 1 for details.
[0056] Table 1 Raw material ratios and process parameters of preparation examples 1.1-1.5
[0057]
[0058] Preparation Example 2 First Graphite Composite Powder
[0059] Preparation Example 2.1
[0060] A first graphite composite powder is prepared by mixing 320kg of 200-mesh graphite powder, 80kg of phenolic resin and 1kg of carbon fiber.
[0061] Preparation Example 2.2
[0062] The first graphite composite powder is prepared by mixing 340kg of 200-mesh graphite powder, 60kg of phenolic resin and 2kg of carbon fiber.
[0063] Preparation Example 2.3
[0064] The first graphite composite powder is prepared by mixing 360kg of 200-mesh graphite powder, 40kg of phenolic resin and 3kg of carbon fiber.
[0065] Preparation Examples 2.4-2.8
[0066] Different from Preparation Example 2.2, in Preparation Examples 2.4-2.8, the carbon fibers were replaced by an equal amount of modified carbon fibers from Preparation Examples 1.1-1.5.
[0067] Preparation Example 3 Second Graphite Composite Powder
[0068] Preparation Example 3.1
[0069] A second graphite composite powder is prepared by mixing 180kg of 200-mesh graphite powder, 15kg of phenolic resin and 0.5kg of carbon fiber.
[0070] Preparation Example 3.2
[0071] The second graphite composite powder is prepared by mixing 190 kg of 200-mesh graphite powder, 10 kg of phenolic resin and 1 kg of carbon fiber.
[0072] Preparation Example 3.3
[0073] The second graphite composite powder is prepared by mixing 200 kg of 200-mesh graphite powder, 5 kg of phenolic resin and 1.5 kg of carbon fiber.
[0074] Preparation Examples 3.4-3.8
[0075] Different from Preparation Example 3.2, in Preparation Examples 3.4-3.8, the carbon fibers were replaced by an equal amount of modified carbon fibers from Preparation Examples 1.1-1.5. Example
[0076] Example 1 Single graphite composite powder, secondary powder making
[0077] Example 1.1
[0078] A fuel cell graphite composite plate is prepared by the following steps:
[0079] S1, raw material granulation: weigh 402 kg of the first graphite composite powder from Preparation Example 2.1 and spread it evenly on a flat plate, dry it at 90° C. for 10 min, and crush it after cooling to obtain composite powder particles with a particle size of 200 mesh;
[0080] S2. Evenly spread the prepared composite powder particles into the mold. After closing the mold, heat and hot press the mold containing the graphite composite powder particles. The temperature is raised from room temperature to 150° C. within 20 minutes and hot pressed for 10 minutes. The hot pressing pressure is 20 MPa to obtain a fuel cell composite graphite plate.
[0081] Examples 1.2-1.5
[0082] Different from Example 1.1, the process parameters in Examples 1.2-1.5 are different, see Table 2 for details.
[0083] Table 2 Process parameters of Examples 1.1-1.5
[0084]
[0085] Examples 1.6-1.7
[0086] Different from Example 1.4, the first graphite composite powder in Examples 1.6-1.7 is obtained in equal amounts from Preparation Examples 2.2-2.3.
[0087] Comparative Example 1
[0088] A fuel cell graphite composite plate is prepared by the following steps:
[0089] 402 kg of the first graphite composite powder from Preparation Example 2.1 was weighed and evenly spread into the mold. After the mold was closed, the mold containing the graphite composite powder was heated and hot pressed from room temperature to 150°C within 20 minutes and hot pressed for 10 minutes at a hot pressing pressure of 20 MPa to obtain a fuel cell composite graphite plate.
[0090] The fuel cell graphite composite plates prepared in Examples 1.1-1.7 and Comparative Example 1 were tested for thickness uniformity, surface resistivity and contact resistance, as shown in Table 3 for details.
[0091] Table 3 Performance test data table of Examples 1.1-1.7 and Comparative Example 1
[0092]
[0093] Combined with Table 3, it can be seen that the graphite composite plates prepared in Examples 1.1-1.7 are superior to the graphite composite plates prepared in Comparative Example 1 in terms of thickness uniformity, surface resistivity, contact resistance and flexural strength. This may be because in Examples 1.1-1.7, the first graphite composite powder is subjected to secondary powder making, so that the phenolic resin is evenly coated on the surface of the graphite powder and cross-linked and cured, thereby forming graphite composite powder particles with uniform particle size, which is convenient for distribution and makes the thickness of the prepared graphite composite plate uniform, and reduces the possibility of wet phenolic resin accumulating on both sides close to the mold during hot pressing, thereby reducing the adverse effect on the contact resistance between the prepared graphite composite plate and the membrane electrode.
[0094] The effects of drying temperature and drying time were investigated in Examples 1.1-1.3. The results showed that the graphite composite plate prepared in Example 1.2 performed better in thickness uniformity, surface resistivity, contact resistance and flexural strength. This indicates that the drying temperature and drying time selected in Example 1.2 are beneficial to improving the performance of the graphite composite plate in thickness uniformity, surface resistivity, contact resistance and flexural strength.
[0095] Taking Example 1.2 as a control, the effects of hot pressing temperature, hot pressing time and hot pressing pressure were investigated in Examples 1.4-1.5. The results showed that the graphite composite plate prepared in Example 1.4 performed better in thickness uniformity, surface resistivity, contact resistance and bending strength. This shows that the hot pressing temperature, hot pressing time and hot pressing pressure selected in Example 1.4 are beneficial to improving the performance of the graphite composite plate in thickness uniformity, surface resistivity, contact resistance and bending strength.
[0096] Taking Example 1.4 as a control, the influence of the raw material ratio of the first graphite composite powder was investigated in Examples 1.6-1.7. The results showed that the graphite composite plate prepared in Example 1.6 performed better in thickness uniformity, surface resistivity, contact resistance and flexural strength, which indicates that the raw material ratio of the first graphite composite powder selected in Example 1.6 is beneficial to improving the performance of the graphite composite plate in thickness uniformity, surface resistivity, contact resistance and flexural strength.
[0097] Example 2 Compounding of graphite composite powder, secondary powder making, and graded hot pressing
[0098] Example 2.1
[0099] A fuel cell graphite composite plate is prepared by the following steps:
[0100] S1, raw material granulation: weigh 201kg of the first graphite composite powder prepared in Preparation Example 2.2 and spread it evenly on a flat plate, dry it at 140°C for 15min, and crush it after cooling to obtain first composite powder particles with a particle size of 200 mesh; weigh 201kg of the second graphite composite powder prepared in Preparation Example 3.1 and spread it evenly on a flat plate, dry it at 140°C for 15min, and crush it after cooling to obtain second composite powder particles with a particle size of 200 mesh;
[0101] S2. Evenly spread the prepared first composite powder particles into the mold. After closing the mold, pre-press the mold containing the first graphite composite powder particles at 30° C. for 5 minutes, and the pre-pressing pressure is 2 MPa. After the pressure is released, evenly distribute the second graphite composite powder particles on the flow field side of the pressed first graphite composite powder. After closing the mold, heat the mold to 160° C. within 35 minutes and hot press for 10 minutes, and the hot pressing pressure is 30 MPa to obtain a graphite composite plate.
[0102] Example 2.2-2.3
[0103] Different from Example 2.1, the second graphite composite powder in Examples 2.2-2.3 is obtained in equal amounts from Preparation Examples 3.2-3.3.
[0104] Example 2.4
[0105] Different from Example 2.2, in Example 2.4, the pre-pressing temperature is 50° C., the pre-pressing time is 10 min, and the pre-pressing pressure is 5 MPa.
[0106] Comparative Example 2
[0107] A fuel cell graphite composite plate is prepared by the following steps:
[0108] 201 kg of the first graphite composite powder from Preparation Example 2.2 was weighed and evenly spread into the mold. After the mold was closed, the mold containing the graphite composite powder was heated and hot pressed from room temperature to 150°C within 20 minutes and hot pressed for 10 minutes at a pressure of 20 MPa. After the pressure was released, 201 kg of the second graphite composite powder obtained in Preparation Example 3.1 was weighed and evenly spread on the flow field side of the pressed first graphite composite powder. After the mold was closed, the mold was heated from room temperature to 160°C within 35 minutes and hot pressed for 10 minutes at a pressure of 30 MPa to obtain a fuel cell composite graphite plate.
[0109] The fuel cell graphite composite plates prepared in Examples 2.1-2.4 and Comparative Example 2 were tested for thickness uniformity, surface resistivity and contact resistance, as shown in Table 4 for details.
[0110] Table 4 Performance test data table of Examples 2.1-2.4 and Comparative Example 2
[0111]
[0112] Combined with Table 4, the graphite composite plates prepared in Examples 2.1-2.4 are superior to the graphite composite plates prepared in Comparative Example 2 in terms of thickness uniformity, surface resistivity, contact resistance and flexural strength. This may be because in Examples 2.1-2.4, the first graphite composite powder and the second graphite composite powder are respectively powdered for secondary use, and the first graphite composite powder particles and the second graphite composite powder particles after secondary powdering are compounded in a 1:1 ratio, which facilitates the distribution of the first graphite composite powder and the second graphite composite powder, and makes the phenolic resin in the obtained graphite composite plate distributed in a gradient, further reducing the possibility of phenolic resin accumulation on both sides close to the mold during hot pressing, and reducing the adverse effects on the contact resistance between the obtained graphite composite plate and the membrane electrode.
[0113] Taking Example 1.6 as a control, the effects of the second graphite composite powder and graded hot pressing were investigated in Examples 2.1-2.3. The results showed that the graphite composite plates prepared in Examples 2.1-2.3 were superior to the graphite composite plates prepared in Example 1.6 in terms of thickness uniformity, surface resistivity, contact resistance and flexural strength. This indicates that the use of a 1:1 compound of the first graphite composite powder and the second graphite composite powder and the use of graded hot pressing to prepare the graphite composite plate is beneficial to improving the performance of the graphite composite plate in terms of thickness uniformity, surface resistivity, contact resistance and flexural strength.
[0114] This may be because in Examples 2.1-2.3, the first graphite composite powder particles of the secondary powder making are pre-pressed, and then the second graphite composite powder particles of the secondary powder making are distributed on the pre-pressed first graphite composite powder particles. At this time, the first graphite composite powder particles are in plate shape, which reduces the possibility of the second graphite composite powder particles being mixed with the first graphite composite powder particles, thereby making the phenolic resin in the prepared graphite composite plate have a gradient distribution and does not affect the bonding force between the first graphite composite powder particles and the second graphite composite powder particles.
[0115] In Examples 2.1-2.3, the influence of the raw material ratio of the second graphite composite powder was investigated. The results showed that the graphite composite plate prepared in Example 2.2 performed better in thickness uniformity, surface resistivity, contact resistance and flexural strength. This shows that the raw material ratio of the second graphite composite powder selected in Example 2.2 is beneficial to improving the performance of the graphite composite plate in thickness uniformity, surface resistivity, contact resistance and flexural strength.
[0116] Taking Example 2.2 as a control, Example 2.4 investigated the effects of pre-pressing pressure, pre-pressing time and pre-pressing temperature. The results showed that the graphite composite plate prepared in Example 2.2 performed better in thickness uniformity, surface resistivity, contact resistance and bending strength. This shows that the pre-pressing pressure, pre-pressing time and pre-pressing temperature selected in Example 2.2 are beneficial to improving the performance of the graphite composite plate in thickness uniformity, surface resistivity, contact resistance and bending strength.
[0117] Example 3 Compounding of composite powder, secondary powder making, graded hot pressing, and modified carbon fiber
[0118] Examples 3.1-3.5
[0119] Different from Example 2.2, the first graphite composite powder in Examples 3.1-3.5 is obtained in equal amounts from Preparation Examples 2.4-2.8.
[0120] Examples 3.6-3.10
[0121] Different from Example 3.4, the second graphite composite powder in Examples 3.6-3.10 is obtained in equal amounts from Preparation Examples 3.4-3.8.
[0122] The fuel cell graphite composite plates prepared in Examples 3.1-3.10 were tested for thickness uniformity, surface resistivity and contact resistance, as shown in Table 5.
[0123] Table 5 Performance test data table of Examples 3.1-3.10
[0124]
[0125] Combined with Table 5, it can be seen that the graphite composite plates prepared in Examples 3.1-3.10 are better than the graphite composite plates prepared in Example 3.1 in terms of thickness uniformity, surface resistivity, contact resistance and flexural strength, which indicates that the use of modified carbon fibers to replace the carbon fibers in the first graphite composite powder and the second graphite composite powder in equal amounts is beneficial to improving the performance of the graphite composite plates in terms of thickness uniformity, surface resistivity, contact resistance and flexural strength.
[0126] In Examples 3.1-3.3, the effect of the raw material ratio of the modified carbon fiber in the first graphite composite powder was investigated. The results showed that the graphite composite plate prepared in Example 3.2 performed better in thickness uniformity, surface resistivity, contact resistance and flexural strength. This indicates that the raw material ratio of the modified carbon fiber selected in Example 3.2 is beneficial to improving the performance of the graphite composite plate in thickness uniformity, surface resistivity, contact resistance and flexural strength.
[0127] Taking Example 3.2 as a control, the effects of mixing temperature and mixing time for preparing modified carbon fibers in the first graphite composite powder were investigated in Examples 3.4-3.5. The results showed that the graphite composite plate prepared in Example 3.4 performed better in thickness uniformity, surface resistivity, contact resistance and flexural strength, which indicates that the mixing temperature and mixing time selected in Example 3.4 are beneficial to improving the performance of the graphite composite plate in thickness uniformity, surface resistivity, contact resistance and flexural strength.
[0128] Taking Example 3.4 as a control, the influence of the raw material ratio of the modified carbon fiber in the second graphite composite powder was investigated in Examples 3.6-3.8. The results showed that the graphite composite plate prepared in Example 3.7 performed better in thickness uniformity, surface resistivity, contact resistance and flexural strength, which indicates that the raw material ratio of the modified carbon fiber selected in Example 3.7 is beneficial to improving the performance of the graphite composite plate in thickness uniformity, surface resistivity, contact resistance and flexural strength.
[0129] Taking Example 3.7 as a control, the effects of mixing temperature and mixing time for preparing modified carbon fibers in the second graphite composite powder were investigated in Examples 3.9-3.10. The results showed that the graphite composite plate prepared in Example 3.9 performed better in thickness uniformity, surface resistivity, contact resistance and flexural strength, which indicates that the mixing temperature and mixing time selected in Example 3.9 are beneficial to improving the performance of the graphite composite plate in thickness uniformity, surface resistivity, contact resistance and flexural strength.
[0130] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a fuel cell graphite composite plate, characterized in that: The following steps are involved: S1, raw material granulation: weigh the first graphite composite powder in proportion and evenly spread it on a flat plate, dry it at 90-150°C for 10-30min, and crush it after cooling to obtain the first composite powder particles with a particle size of 200±100 mesh; weigh the second graphite composite powder in proportion and evenly spread it on a flat plate, dry it at 90-150°C for 10-30min, and crush it after cooling to obtain the second composite powder particles with a particle size of 200±100 mesh; the graphite composite powder includes the first graphite composite powder and the second graphite composite powder. Composite powder, the weight ratio of the first graphite composite powder to the second graphite composite powder is 1: (1 ± 0.1), the first graphite composite powder is prepared by mixing 160-180 parts of 200 ± 100 mesh graphite powder, 20-40 parts of phenolic resin and 0.5-1.5 parts of filler, and the filler includes carbon fiber; the second graphite composite powder is prepared by mixing 180-200 parts of 200 ± 100 mesh graphite powder, 5-15 parts of phenolic resin and 0.5-1.5 parts of filler, and the filler includes carbon fiber; S2. Evenly spread the prepared first composite powder particles into a mold, place the mold containing the first graphite composite powder particles at a temperature of 30-50° C. for pre-pressing for 5-10 min, and the pre-pressing pressure is 2-5 MPa. After the pressure is released, evenly distribute the second graphite composite powder particles on the flow field side of the pressed first graphite composite powder, and after closing the mold, place it again at a temperature of 150-180° C. for hot pressing for 30-60 min, and the hot pressing pressure is 20-40 MPa to obtain a graphite composite plate.
2. The method for preparing a fuel cell graphite composite plate according to claim 1, characterized in that: The carbon fiber is a modified carbon fiber, which is prepared by grafting carboxymethyl cellulose onto the carbon fiber through 3-aminopropyltriethoxysilane.
3. The method for preparing a fuel cell graphite composite plate according to claim 2, characterized in that: The weight ratio of the carboxymethyl cellulose, 3-aminopropyltriethoxysilane and carbon fiber is 1:(92-100):(2-4).
4. The method for preparing a fuel cell graphite composite plate according to claim 3, characterized in that: The modified carbon fiber is prepared by the following steps: A1. Surface oxidation: The carbon fiber is placed in a concentrated nitric acid solution, treated at room temperature for 30-150 minutes, washed to a pH of 7±1, and then dried to obtain a surface-treated carbon fiber; A2. Silanization: Dissolve 3-aminopropyltriethoxysilane in a methanol solution with a mass fraction of 90±1% according to a certain proportion and mix well. Add the obtained surface-treated carbon fiber into the solution and mix for 2±1h, then filter out the fiber and dry it for 24±1h to obtain silanized carbon fiber. A3. Graft modification: Carboxymethyl cellulose is added to deionized water in proportion and mixed evenly, silanized carbon fiber is added to the mixture, and mixed at a temperature of 60-80° C. for 2-3 hours, filtered and dried to obtain modified carbon fiber.
5. A fuel cell graphite composite plate, characterized in that: The fuel cell graphite composite plate is prepared by the method for preparing the fuel cell graphite composite plate according to any one of claims 1 to 4.
Citation Information
Patent Citations
Double-resin-system composite graphite for bipolar plate of fuel cell as well as preparation method and application of double-resin-system composite graphite
CN114976096A